Risk-Taking, Internal Locus of Control, and Entrepreneurial Intentions: The Mediating Effect of Attitudes toward Entrepreneurship - Setiawan, Ananda; Rahmattullah, Muhammad; Anita, Anita; Jainab, Jainab (Soedirman Economics Education Journal, 2025)
This research aims to find out how Risk taking Propensity, Internal Locus of Control, Perceived Barriers, and Received Support influence Entrepreneurial Intention through Attitude Towards Entrepreneurship on students in Banjarmasin. In In this research, the method used is a quantitative method with SEM-PLS analysis to determine the phenomenon being studied. This research questionnaire was built based on a literature review and modified from previous research. The respondents for this research were 310 active students at universities in South Kalimantan. The research results reveal that Risk Taking Propensity and Internal Locus of Control contribute positively and significantly to Attitude Towards Entrepreneurship. Then Attitude Towards Entrepreneurship, RTP, and RS contribute positively and significantly to Entrepreneurial Intention. Meanwhile, Internal Locus of Control and Perceived Barriers do not contribute positively and significantly to Entrepreneurial Intention. This is the first step for students to realize that PB needs to be watched out for, students also need to be aware of the presence of Internal Locus of Control and Perceived Barriers and Internal Locus of Control need to be reconstructed so that they have an impact on entrepreneurial intentions.